Variable stars in the field of the young open cluster Roslund 2. Issue Volume 9:Issue S301(2013) (18th February 2014) - Sowicka, P.; Handler, G.; Taubner, R.; Brunner, M.; Passegger, V.-M.; Bauer, F.; Paunzen, E.
Abstract: The study of variable stars in open clusters via asteroseismology is a powerful tool for the study of stellar evolution and stars in general. That is because stars in clusters can be assumed to originate from the same interstellar cloud, so they share similar properties such as age and overall metallicity. We performed a search for variable stars in the field of the young open star cluster Roslund 2, with photoelectric and CCD photometry acquired at two different telescopes. Within the resulting light curves we have found 12 variable stars. Our measurements confirm three previously known variables.